2016
DOI: 10.1039/c5ja00442j
|View full text |Cite
|
Sign up to set email alerts
|

Complementary HPLC-ICP-MS and synchrotron X-ray absorption spectroscopy for speciation analysis of chromium in tobacco samples

Abstract: This paper provides first quantitative speciation data for chromium in tobacco and tobacco smoke by using complementary HLPC-ICP-MS and XANES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Cuello et al also attempted speciation of chromium in mainstream cigarette smoke using HPLC-ICP-MS and synchrotron X-ray absorption spectroscopy. 23 They reported that individual chromium oxidation states could not be determined in water leachates of the mainstream smoke TPM using HPLC-ICP-MS. TPM and chromium(III) oxide are poorly water soluble, so this was useful but not unexpected information. Cuello et al also reported that chromium(VI) was highly unstable when spiked into TPM, confirming that strongly oxidizing chromium(VI) is not stable in a reducing medium such as TPM.…”
Section: Resultsmentioning
confidence: 99%
“…Cuello et al also attempted speciation of chromium in mainstream cigarette smoke using HPLC-ICP-MS and synchrotron X-ray absorption spectroscopy. 23 They reported that individual chromium oxidation states could not be determined in water leachates of the mainstream smoke TPM using HPLC-ICP-MS. TPM and chromium(III) oxide are poorly water soluble, so this was useful but not unexpected information. Cuello et al also reported that chromium(VI) was highly unstable when spiked into TPM, confirming that strongly oxidizing chromium(VI) is not stable in a reducing medium such as TPM.…”
Section: Resultsmentioning
confidence: 99%
“…There are no data on the extractability of other α-emitters from STPs. It is also difficult to estimate the solubility of these species in tobacco because the exact chemical forms are unknown: recent work has demonstrated that inorganic metalloids in tobacco can be present in multiple chemical states [ 49 ] and with differing solubilities [ 50 ]. Environmental studies have shown that radium is only moderately soluble in water, but is most soluble under chloride-rich reducing aqueous systems with a high total content of dissolved solids, a condition that might relate to STPs that have a high salt and water content [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 The most commonly performed analytical strategy for Cr monitoring involves two steps: (1) collection of water samples at the eld site followed by storage and transportation it to the laboratory, and (2) analysis using atomic spectrometry aer separation by one of a number of online or offline separation approaches, such as solid-phase extraction, liquid-liquid extraction, cloud-point extraction, or co-precipitation. [8][9][10][11][12][13][14] However, accurate speciation of Cr in natural water bodies is difficult, mainly due to matrix complexity and the instability of Cr redox species during sample collection, transport, and analysis. 15 For example, Meeravali et al 16 found that the concentration of Cr(III) increased by 135% and that of Cr(VI) decreased by 75% within 24 h when lake water samples were collected and stored at 4 C. This demonstrates that the concentrations of chemical species in particular redox states are inherently unstable in water and subject to change by re-equilibration upon reaction with other dissolved components.…”
Section: Introductionmentioning
confidence: 99%